2010
DOI: 10.3354/ab00274
|View full text |Cite
|
Sign up to set email alerts
|

Methods for sampling benthic macroinvertebrates in tropical lentic systems

Abstract: Reliable quantitative methods for sampling invertebrate communities are critical for effective freshwater biomonitoring. We tested a range of devices and protocols for sampling benthic macroinvertebrates in shallow tropical lakes; this is the first time this has been attempted in Southeast Asia. First, a pilot study to identify a suitable artificial substrate and colonisation period was conducted. Coconut brushes combined with split palm fronds attracted the greatest macroinvertebrate abundance and richness. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Findings reported in our study are consistent (at least superficially) with the highly influential, albeit controversial hypothesis (Polis 1991) which posits that food web structures are relatively constant (Martinez 1992). In these earlier studies, connectance values were shown to be scaleinvariant, ranging from 0.05 to 0.30 (Dunne et al 2002a), and converging at a mean of 0.14 (Martinez 1992).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings reported in our study are consistent (at least superficially) with the highly influential, albeit controversial hypothesis (Polis 1991) which posits that food web structures are relatively constant (Martinez 1992). In these earlier studies, connectance values were shown to be scaleinvariant, ranging from 0.05 to 0.30 (Dunne et al 2002a), and converging at a mean of 0.14 (Martinez 1992).…”
Section: Discussionsupporting
confidence: 91%
“…Primary producers were sampled via leaf clipping of numerically dominant taxa (i.e., for riparian plants and grasses), horizontal trawls with nets of mesh size 80 μ m (i.e., for phytoplankton via seston samples), and scraping of submerged rocky surfaces (i.e., for periphyton). Invertebrate specimens were collected with submerged colonizers deployed at a fixed depth of 1 m over a 1‐month period (i.e., for benthic invertebrates; Loke et al ) and by conducting horizontal trawls with nets of 80 μ m mesh sizes (i.e., for planktonic invertebrates). We collected fishes using a combination of cast netting, trapping, and electrofishing.…”
Section: Methodsmentioning
confidence: 99%
“…Adult specimens for some species were also serendipitously obtained from Malaise traps (Singapore). Some larvae were collected with kick‐nets, sieves and coconut brush samplers (Loke et al ., ). Many of the samples were collected for biomonitoring purposes by the Tropical Marine Science Institute (TMSI).…”
Section: Methodsmentioning
confidence: 97%
“…Artificial substrates have been shown to be effective in enhancing structural complexity in ecological engineering (Bulleri and Chapman, 2010;Chapman and Blockley, 2009) and restoration projects (Larkin et al, 2006). They are also widely used in experimental studies testing the effects of habitat complexity on species diversity and community structure (Larkin et al, 2006;Loke et al, 2010;Matias et al, 2013). At the point of construction, artificial substrates are clearly not dynamic; hence only informational complexity can be incorporated into them (usually into their topography or matrix).…”
Section: Operational Definition Of Informational Complexitymentioning
confidence: 99%